2013
DOI: 10.3390/molecules181215490
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Separation of Six Rhynchophylla Alkaloids from Uncaria macrophylla Wall by pH-Zone Refining Counter-Current Chromatography

Abstract: pH-Zone refining counter-current chromatography was successfully applied to the preparative isolation and purification of six alkaloids from the ethanol extracts of Uncaria macrophylla Wall. Because of the low content of alkaloids (about 0.2%, w/w) in U. macrophylla Wall, the target compounds were enriched by pH-zone refining counter-current chromatography using a two-phase solvent system composed of petroleum ether-ethyl acetate-isopropanol-water (2:6:3:9, v/v), adding 10 mM triethylamine in organic stationar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The most widely distributed UR alkaloid RHY is only found in 24 kinds of traditional Chinese medicines. The contents of hirsuteine, hirsutine and RHY were 17.14, 12.86 and 58.21 mg/g of UR total alkaloids, respectively ( Zhang et al, 2013 ). Another study showed that hirsuteine, hirsutine, isocorynoxeine, IRN and RHY were 12.75, 16.25, 13.50, 11.50 and 8.75 mg/g of UR refined alkaloids ( Feng et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most widely distributed UR alkaloid RHY is only found in 24 kinds of traditional Chinese medicines. The contents of hirsuteine, hirsutine and RHY were 17.14, 12.86 and 58.21 mg/g of UR total alkaloids, respectively ( Zhang et al, 2013 ). Another study showed that hirsuteine, hirsutine, isocorynoxeine, IRN and RHY were 12.75, 16.25, 13.50, 11.50 and 8.75 mg/g of UR refined alkaloids ( Feng et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several enrichment methods have been reported, including conventional column chromatography [10], acid-base extraction [11,12], pH-zone-refining CCC [13] and extraction by two-phase solvent system used for pH-zone-refining CCC [14]. For the conventional column chromatography, the procedure was tedious and required several chromatographic steps, which can result in the irreversible adsorptive loss of sample in the stationary phase and often entail artifact formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Miq. ex Havil (UR) is an important traditional herbal medicine and its alkaloids have attached increasing attention due to their notable effect, low toxicity and few adverse effects [13]. UR has been mainly used for treating the cardiovascular and central nervous systems disorder, such as lightheadedness, convulsions, numbness, hypertension and so on, of which the indole alkaloids were reported as the active pharmacological components [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for analysing hirsutine and hirsuteine including high-performance liquid chromatography (HPLC), liquid chromatography-tandem mass spectrometry (LC-MS/MS), pH-zone refining counter-current chromatography (CCC) and so on. [10][11][12][13] However, all these methods have their own limitations. HPLC and LC-MS/MS methods only determined the hirsutine in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these two methods need longer analysis time and demand higher cost of equipment. The pH‐zone‐refining CCC method was developed for the preparative separation of hirsutine and hirsuteine in UR, however, it needs longer analysis time (more than 30 min) and large amounts of organic solvent. Compared with these analysis technologies, the method we developed by capillary electrophoresis (CE) has numerous advantages such as high separation selectivity, rapid analysis, efficiency, small sample size and low consumption.…”
Section: Introductionmentioning
confidence: 99%